COVID-19: A new meaning of telework: Based on an online survey of the employee’s perceptions - Calhau, João Afonso Godinho (2022)
The Covid-19 pandemic forced organizations to adopt telework as the only solution to maintain activity in a scenario of mandatory confinement. The pandemic has created room for research of individual and organizational options. Our study explores the level of satisfaction of teleworkers on several dimensions. Additionally, it compares two types of teleworkers, those who were already working in this regime and those who joined remote work during the pandemic. This exploratory research is based on an online survey, applied in 2021, which allowed the collection of data on 156 teleworkers. The empirical results show a very positive perception regarding individual productivity, flexibility and autonomy in scheduling work tasks, work-life balance, due to the flexibility that teleworking allows. These are considered the main advantages of teleworking that have become mandatory. On the other hand, isolation emerges as a negative aspect within the domains studied. In addition, the boundaries between work and family responsibilities have become blurred, which can cause conflict between these two roles. Regarding the organization, respondents admit that managers played a more difficult role in managing their teams remotely during the pandemic. Teleworkers consider, however, that there was reliable support, even remotely. Regarding the future, the workers who participated in the study consider the experience positive and intend to continue teleworking in a post-pandemic future, but in a hybrid mode.